2013
DOI: 10.1111/obr.12019
|View full text |Cite
|
Sign up to set email alerts
|

Chronobiology, endocrinology, and energy‐ and food‐reward homeostasis

Abstract: Energy- and food-reward homeostasis is the essential component for maintaining energy balance and its disruption may lead to metabolic disorders, including obesity and diabetes. Circadian alignment, quality sleep and sleep architecture in relation to energy- and food-reward homeostasis are crucial. A reduced sleep duration, quality sleep and rapid-eye movement sleep affect substrate oxidation, leptin and ghrelin concentrations, sleeping metabolic rate, appetite, food reward, hypothalamic-pituitary-adrenal (HPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 136 publications
(277 reference statements)
0
70
0
3
Order By: Relevance
“…Given the 3-hour shift in bedtimes, a circadian influence on observed differences in leptin is also possible. 33 Differences observed in measured weight provide a potentially compelling link between differences in sleep, reported dietary intake, and fasting leptin. Similar to a laboratory study with adults, 8 compared with the end of the decrease sleep condition, on average children weighed ∼0.22 kg less at the end of the increase sleep condition.…”
Section: Figurementioning
confidence: 99%
“…Given the 3-hour shift in bedtimes, a circadian influence on observed differences in leptin is also possible. 33 Differences observed in measured weight provide a potentially compelling link between differences in sleep, reported dietary intake, and fasting leptin. Similar to a laboratory study with adults, 8 compared with the end of the decrease sleep condition, on average children weighed ∼0.22 kg less at the end of the increase sleep condition.…”
Section: Figurementioning
confidence: 99%
“…56,57 The reward system is also intrinsically related to bodyenergy regulation. This system is thought to underlie alterations in some eating behaviours, 58,59 and it has received increasing interest in recent years, being considered a key element in the development and maintenance of anorexia nervosa. 2,60 Actually, several studies have shown that patients with this disorder present deviant responses to the reinforcing characteristics of several types of disorder-relevant and nonrelevant stimuli and that such abnormal responses are probably implicated in the persistence of the pathological behaviour.…”
Section: Changes In the Fornixmentioning
confidence: 99%
“…Another advantage of having a healthier chronotype has to do with the well-established link between biological rhythms and obesity (Gonnissen et al, 2013), something to keep in mind considering that weight gain is a common -and difficult to treat-problem in people with BD and has also been related with a poor prognosis of the illness (Fagiolini et al, 2003). Last, if we consider the increase morbidity described for the bipolar population, it is remarkable the relationship between alterations in circadian rhythms and increased lipid peroxidation (which it's related to increased likelihood of Alzheimer disease and several types of cancer).…”
Section: Discussionmentioning
confidence: 99%